Defining a state-owned enterprise in international investment agreements - MCLAUGHLIN, Mark (Institutional Knowledge at Singapore Management University, 2019)
The objective of this article is to establish a unified conceptual framework for State-owned enterprises in international investment law. I hope to furnish drafters and negotiators with the tools to define such enterprises in accordance with their policy concerns. The central thesis is that five definitional criteria must be considered: (i) separate legal personality; (ii) extent and form of control; (iii) eligible governmental units; (iv) nature of activity; and (v) purpose of activity. While variations within each criterion can reflect the policy choices of contracting parties, failure to adequately delimit the boundaries of all five will confer discretion on arbitrators to do so.Application of this framework to existing international investment agreements reveals that many bilateral investment treaties are insufficiently precise as to the definition of State-owned enterprises. However, the Trans Pacific Partnership addresses all five criteria, and limits the scope of covered entities to those that are ‘principally engaged in commercial activities’ and have an ‘orientation towards profit making’. China’s strategic initiatives could necessitate a response that would further fragment the international investment regime. Furthermore, interpretive issues remain in relation to the scope of ‘effective influence’ and determining the purpose of investment activity.